Pengaruh Profitabilitas, Struktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Perusahaan Pertambangan - Khaldea Azzahra; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The objective to be achieved in this research is to know the influence of profitability, capital structure and firm size on firm value in mining companies listed on the Indonesia Stock Exchange in 2017-2019. This research using secondary data from annual financial statement of mining company listed on Indonesia Stock Exchange from 2017 to 2019. The sample used in the research are 38 companies that meet the criteria based on purposive sampling and used 3 periods of each companies so that resulting in 114 sample. The result of this research indicates that profitability has no effect on the firm value. While the capital structure and firm size have effect on the firm value.